Soy-based adhesive cross-linked by melamine–glyoxal and epoxy resin. Issue 19 (1st October 2016) - Wu, Zhigang; Lei, Hong; Cao, Ming; Xi, Xuedong; Liang, Jiankun; Du, Guanben
Abstract: To develop a soy-based adhesive with good water resistance, non-toxic melamine–glyoxal resin (MG) prepared in the laboratory was used as a cross-linker of soy-based adhesive. The FT-IR and ESI-MS results showed that there was a reaction between melamine and glyoxal. The resulted –CH–OH– groups could be the possible reactive groups for the cross-linking of soy-based adhesive. The wet shear strength of soy-based plywood indicated that the water resistance of soy adhesive cross-linked by MG improved with respect to that with no cross-linker, although it was not good enough to satisfy the relative standard. With the optimized preparation procedures for plywood, specifically, press temperature 180 °C, press time 3 min and resin loading 280 g m −2, type I soy-based plywood could be prepared with a hybrid cross-linker, namely 12%MG + 2% epoxy resin (EPR). The DSC results showed that the reaction between soy-based adhesive and the hybrid cross-linker MG + EPR was very complex.